Correlation of Learning Styles, Parental Roles, and Gadget Use with Physical Education Learning Outcomes at SMK Muhammadiyah 2 Semarang - Ardian Bagus Firman Syah; ipang setiawan (Universitas Negeri Semarang, 2026)
Based on observations and interviews conducted at SMK Muhammadiyah 2 Semarang, it was found that teachers have not been able to identify all student learning styles. In addition, limited parental involvement and excessive gadget use contribute to low student learning outcomes. This study aims to determine whether there is a correlation between factors that influence student learning outcomes at SMK Muhammadiyah 2 Semarang. The research design employed a descriptive correlational approach using quantitative methods. The research sample consisted of all students at SMK Muhammadiyah 2 Semarang. Data collection methods included observation, interviews, and questionnaires. The results indicate that there is a correlation between learning styles and physical education learning outcomes of 26%. A correlation between parental roles and physical education learning outcomes was found to be 50%. Gadget use was correlated with physical education learning outcomes at 24%. The combined correlation between learning styles and parental roles with physical education learning outcomes was 26 %. The correlation between learning styles and gadget use with physical education learning outcomes was 25%. The correlation between parental roles and gadget use with physical education learning outcomes was 36%. Furthermore, the combined correlation of parental roles, learning styles, and gadget use with physical education learning outcomes at SMK Muhammadiyah 2 Semarang reached 70%.